Jenama dan Citra: Strategi Aktivasi Merek Kabupaten Ponorogo Melalui “Fantastic Ponorogo” - Mela Siti Maisaroh; Rhesa Zuhriya Briyan Pratiwi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2021)
Each region has characteristics in a number of tourist destinations that it manages. In this case, Ponorogo Regency is famous for several tourist objects, those referring to natural tourism, cultural tourism, religious tourism, to tourism in a special concept. Since 2019, Ponorogo Regency has carried out its tourism branding through a special brand